Police organizational failure and decoupling: Identifying precursors to failure through the rampart commission - Johnson, Amanda (International journal of police science & management, 2019)
In criminal justice organizations, organizational failure can have catastrophic, often tragic, repercussions. Through the theoretical framework of coupling, this work studies a past organizational failure, the Rampart incident in Los Angeles, and determine what organizational characteristics led to the failure. Using case study analysis, this article investigates circumstances leading to organizational dysfunction, the categories of failure are coded and analyzed to determine precursors to organizational failure. Ultimately, this article shows that police organizational failure is not simply the case of misconduct or deviance, but rather a natural occurrence that can be precipitated by organizational precursors. From these precursors, it should be possible to develop a template which could identify organizations at risk for failure.